Green tourism as the future’s strategic direction? - Varga-Nagy, Adrienn; Káposzta, József; Nagy, Henrietta (Studia Mundi – Economica, 2017)
Most settlements consider tourism as a general method for the way out from their situation that can be applied in any situation. If national and international economic strategies are overviewed, tourism can be found in almost all of them, since all regions have values that are worth to introduce. However, if only the attraction is given, it is not enough for the success, not even for the development if it is not carefully planned. Planning is difficult because of the quickly changing economic environment that is hard to follow carefully. Planning in tourism means the use of resources of state, municipality, non-profit and private sector as efficient as possible as well as aims to reach the highest possible profit. All this has to be carried out as meeting the sustainable development principles while paying enough attention on the trends in analyses. Based on the abovementioned principles, such development directions focusing on the protection of natural values and green/ecotourism as a strategic sector could be involved in development strategies.